L’attachement aux lieux dans les conflits liés à l’environnement sur le littoral : une ressource pour leur régulation - Anne Cadoret (VertigO)
This contribution aims to identify multiple territorialities and their roles in environmental antagonistic dynamics and characterize the signs of place attachement that we observed in various studies on French coastal zone. Our research shows that place attachment can be revealed by an hypersensitivity of individuals or groups and the intensity of their reactions, the structuring of collectives, violence of acts of opposition, signs in the public spaces, the use of possessive adjectives in stakeholders arguments. These signs of place attachment reveal territorialities which are important to consider for conflict regulation because their lack of consideration very frequently lead, in our case studies, to a radicalisation of the conflict.